Katecheci parafii w Sokołowie Małopolskim na początku XX wieku (1900-1920) - Walicki, Bartosz (Archiwa, Biblioteki i Muzea Kościelne, 2011)
In the two first decades of the 20th century, 5 regular catechists worked in the St John Baptism Parish of Sokołów Małopolski: the Rev. Wojciech Karaś (1900-1902), the Rev. Józef Szpila (1903–1904), the Rev. Leopold Augustyn (1904-1907), the Rev. Michał Klajewicz (1909-1911) and the Rev. Stanisław Woźny (1912-1920). Those priests mainly taught religion in the five-grade coeducational school in Sokołów Małopolski, the school which was divided into a female and male one in 1913. Apart from this, they helped parish priests with pastoral work. At that time the parish priests were the Rev. Franciszek Stankiewicz (1898-1916), the Rev. Wojciech Blajer (1916) and the Rev. Leon Szado (1916-1934). The article presents biographical entries of the above-mentioned catechists. Two of them, the Rev. Michał Klajewicz and the Rev. Stanisław Woźny died in this parish and were buried in the cemetery of Sokołów. The Rev Leopold Augustyn and the Rev. Stanisław Woźny are especially remembered due to their work for this parish. Apart from pastoral work, they were also active on the social plane. The former one was the cofounder of the the Stefczyk Fund in Sokołów and the latter one worked with the local young people. Another significant catechist, who became renowned for his preacher’s talent, was the Rev. Wojciech Karaś.